2015
DOI: 10.1021/ed500344c
|View full text |Cite
|
Sign up to set email alerts
|

Using a Microscale Approach To Rapidly Separate and Characterize Three Photosynthetic Pigment Species from Fern

Abstract: A rapid separation of three photosynthetic pigments (chlorophyll a and b and xanthophyll) from fern (Polystichum acrostichoides) is described using microscale solvent extraction and traditional thin layer chromatography that minimizes use of harmful chemicals and lengthy procedures. The experiment introduces students to the concepts of extraction and separation of compounds. Combined with absorption and fluorescence spectroscopy using a plate reader, this laboratory experiment demonstrates the concept of light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…All faecal samples collected in this study showed similar pro le and trends. Two distinct bands were observed around 576 nm and 670 nm, which were previously found to be associated with Hb and chlorophyll, respectively (41,49,50). Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387-609 nm to limit the effects of the 670 nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 83%
“…All faecal samples collected in this study showed similar pro le and trends. Two distinct bands were observed around 576 nm and 670 nm, which were previously found to be associated with Hb and chlorophyll, respectively (41,49,50). Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387-609 nm to limit the effects of the 670 nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 83%
“…All faecal samples collected in this study showed similar pro le and trends. Two distinct bands were observed around 576 nm and 670 nm, which were previously found to be associated with Hb and chlorophyll, respectively [42,51,52]. Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387 -609 nm to limit the effects of the 670 nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 83%
“…The selection of a suitable analytical method for the identification and quantification of pigments from the plant matrix depends on the characteristics of required data (Dudek, Strzelewicz, Krasowska, Rybak & Turczyn, 2014). The most frequently used instrumental methodologies are the UV-VIS spectrophotometry, fluorescence spectroscopy and chromatography (Garber, Odendaal & Carlson, 2013;West & Rauch, 1994;Ayudhya, Posey, Tyus & Dingra, 2015;Johnston, Scaggs, Mallory, Haskett, Warner, Brown, et al, 2013;Galloway, Bretz & Novak, 2015;Rollins, 1963;Lalitha, 1994;Kimbrough, 1992;Valverde, This & Vignolle, 2007). Each of these techniques has several advantages; however, the UV-Vis spectrophotometry is the most suitable for the routine determination of the pigment concentration in the extract from the mixed plant samples, as it generally does not require complicated separation and purification processes.…”
Section: Natural Pigmentsmentioning
confidence: 99%